Understanding Features of Education: Essential in Progression of Individuals (Indian Journal of Management and Language (IJML), 2024)
The individuals, belonging to all communities, categories and socio-economic backgrounds have recognized the importance of education on a comprehensive basis. They are getting enrolled in educational institutions of all levels. Within rural communities, these are not in a well-developed state, whereas, within urban communities, these are well-developed, hence, individuals are migrating to urban communities to acquire education. As a consequence of acquiring an efficient understanding of features of education, progression will take place of individuals. Hence, it is of utmost significance for all individuals to acquire the meaning of features of education. These highlight how education is useful to individuals in bringing about improvements in overall personality traits and standards of living. Furthermore, the information that is generated through acquiring good-quality education needs to be put into practice in order to promote well-being of family and community members. Furthermore, living conditions of the individuals will be enhanced. When women, belonging to disadvantaged sections of the society acquire education, they will render an important contribution in bringing about improvements in their overall quality of lives. Therefore, in order to lead to up-gradation of overall standards of living and achieve desired goals and objectives, one needs to acquire an understanding of features of education. The main concepts that are taken into account in this research paper are, features of education, understanding features of education is facilitating in promoting enrichment of living conditions and understanding features of education is essential in promoting women empowerment.